2019
DOI: 10.29137/umagd.507264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solidification Rate on Microstructure and Mechanical Properties with Sb at Different Ratio of AZ91 Quality Mg Alloy

Abstract: Öz Mevcut kullanım alanları gün geçtikçe artış gösteren Mg alaşımlarının, teknolojik gelişmelere uyum sağlayabilmesi için mekanik özellikler bakımından daha fazla geliştirilmesi gerekliliği ortaya çıkmıştır. Günümüzde çözünebilir biyo-malzeme olarak sağlık alanında da kullanılmaya başlayan Mg ve alaşımlarına kazandırılan fiziksel ve mekanik özellikler malzemenin kullanım ömrünü tayin etmektedir. Dolayısıyla bu çalışmada, AZ91 serisi Mg alaşımına farklı oranlarda (%0.2-%0.5 ve %1.0) Sb elementi ilavesi ve katıl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Then, it was determined that the eutectic phase intervals in the image are between 180 and 300 degrees according to the Hue component of the HSL color space shown in Fig. (6), and a Hue filter function was developed accordingly, as shown in Algorithm 1. Thus, all pixel areas other than the eutectic phases are painted white, removing unnecessary details on the image.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Then, it was determined that the eutectic phase intervals in the image are between 180 and 300 degrees according to the Hue component of the HSL color space shown in Fig. (6), and a Hue filter function was developed accordingly, as shown in Algorithm 1. Thus, all pixel areas other than the eutectic phases are painted white, removing unnecessary details on the image.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…There have been some studies on improving the mechanical properties of AZ91 alloys by alloying. Elen, in his study, reported that the mechanical properties of 𝑆𝑏 and 𝐵𝑖 elements added at different rates in the AZ91 alloy improved [3]. Candan et al, in their studies, found that the 𝑇𝑖 element increases the mechanical properties (tensile stress up to 18% and yield stress up to 47%) [4].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations